Analisis Pengaruh Desentralisasi Fiskal Terhadap Pertumbuhan Ekonomi di Kabupaten/Kota Provinsi Jawa Timur - May Yola Shofiul Eka Nurlaili (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
This study aims to determine the effect of Fiscal Decentralization as measured from sources of revenue, namely Regional Original Income, General Allocation Funds, Special Allocation Funds and from Expenditure Sources, namely Capital Expenditures on Economic Growth. The analytical method used is a quantitative approach and the data used is panel data by producing the best model, namely the Fixed Effect Model (FEM). The results showed that fiscal decentralization was measured by the revenue indicator, namely local revenue (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK) have a significant and positive effect on regional economic growth, while for fiscal decentralization as measured by capital expenditures, the results have a significant and negative effect on regional economic growth. in the Regency/City Province. East Java.